Global ozone loss following extreme solar proton storms based on the July 2012 coronal mass ejection - Kalakoski, Niilo; Verronen, Pekka T.; Szeląg, Monika E.; Jackman, Charles H. (Nature Publishing Group, 2023)
Large solar coronal mass ejections pose a threat in the near-Earth space. As a cause of extreme periods of space weather, they can damage satellite-based communications and create geomagnetically induced currents in power and energy grids. Further, the solar wind energetic particles can reduce the protecting layer of atmospheric ozone and pose a threat to life on Earth. The large coronal mass ejection (CME) of July 2012, although directed away from the Earth, is often highlighted as a prime example of a potentially devastating super storm. Here we show, based on proton fuxes recorded by the instruments aboard the STEREO-A satellite, that the atmospheric response to the July 2012 event would have been comparable to those of the largest solar proton events of the satellite era. Signifcant impact on total ozone outside polar regions would require a much larger event, similar to those recorded in historical proxy data sets. Such an extreme event would cause long-term ozone reduction all the way to the equator and increase the size, duration, and depth of the Antarctic ozone hole. The impact would be comparable to predicted drastic and sudden ozone reduction from major volcanic eruptions, regional nuclear conficts, or long-term stratospheric geoengineering.